Internalization of Profil Pelajar Pancasila Strengthening Project in Scout Extracurricular at Elementary School - Atibul Qulub, Ifta; Suttrisno, Suttrisno; Yuli Amreta, Midya (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
In this modern era, the nature and spirit of Pancasila among students have begun to decline. This research aims to describe the internalization of student profiles related to Pancasila values in Scout extracurricular activities. The approach in this research is qualitative. The research location is at Kalicilik State Elementary School, Bojonegoro Regency. Data sampling was carried out by purposive sampling. Data collection methods involved observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data display, and conclusion drawing. Data validity was guaranteed through the application of source triangulation, technique triangulation, and time triangulation techniques. The results showed that the internalization of student profiles related to Pancasila values in extracurricular Scouting activities was carried out through various methods, including involving students in ceremonial activities, routine exercises, and organizing Day Camps (PERSARI) and games. Character values in ceremonial activities are discipline, religion, and responsibility. The character values in training activities are marching training (discipline, leadership spirit, unity and responsibility), character values in PERSARI activities are independence, hard work, social care, and environmental care. The character values in the game are social care, creativity, responsibility, and tolerance.